2006
DOI: 10.1179/174329306x84382
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on friction welding of sintered P/M steel preforms to wrought mild steel

Abstract: Continuous drive friction welding studies on sintered powder metallurgical (P/M) steel preformswrought mild steel combination are reported in the present study. The work is a preliminary study to optimise the friction welding parameters and data generated by the present work is expected to contribute to friction welding of dissimilar and similar sintered P/M preforms to wrought metals or sintered P/M preforms -a planned future research work. Sound welds were obtained with all welding parameter combinations stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Furthermore, a sound joint such as the base metal fracture without crack was made by the autocompleting friction welding method when the CSF value nearly equaled to one. Rao et al 90 reported on the continuous drive friction welding of sintered P/M steel preforms to wrought mild steel. The present investigation aims at understanding the FW characteristics of sintered P/M steel preformswrought mild steel dissimilar metal welds.…”
Section: Friction Welding Of Steel Alloys With Other Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a sound joint such as the base metal fracture without crack was made by the autocompleting friction welding method when the CSF value nearly equaled to one. Rao et al 90 reported on the continuous drive friction welding of sintered P/M steel preforms to wrought mild steel. The present investigation aims at understanding the FW characteristics of sintered P/M steel preformswrought mild steel dissimilar metal welds.…”
Section: Friction Welding Of Steel Alloys With Other Metalsmentioning
confidence: 99%
“…This can be achieved with a compressive rubbing force below that which causes the ceramic to fracture. Aluminium, especially pure aluminium, will 30 Sizes of workpieces for a joint system I and b joint system II 91 31 Schematics of FW 93 29 Microhardness versus distance data from locations 90 bond to aluminium oxide and magnesium for yttrium oxide stabilised zirconium oxide ceramics. The process can be carried out using conventional FW apparatus but under a protective atmosphere to avoid metal oxidation.…”
Section: Friction Welding Of Ceramicsmentioning
confidence: 99%
“…For some special applications, it is necessary to join super-Ni/NiCr laminate to one similar or dissimilar material as integrated components [1][2][3]. Therefore, weldability of super-Ni/NiCr laminate must be well established.…”
Section: Introductionmentioning
confidence: 99%